GENERAL ANATOMY OF THE ORAL CAVITY - Прилуцький, О.К. (World of Medicine and Biology, 2013)
The lecture is devoted to the structure of the human oral cavity. Attention is paid to the structure of the mucosa in different parts of the oral cavity, the structural features of the major and minor salivary glands and their function. We describe the internal structure of the tongue, muscle of the tongue, their function, and external structure of the tongue. Also, much of the lecture is devoted to the teeth: the structure of hard tissues that form the teeth structure and differences of various groups of teeth. Represent the identity of the tooth right or left side. The lecture is useful for students, dentists and practitioners.
Keywords: mouth; gums; palate; tongue; salivary glands; teeth